Industrial training report at Kumpulan Wang Persaraan / Muhammad Aiman Najmi Muhamad Murad - Muhamad Murad, Muhammad Aiman Najmi (Faculty of Business and Management, 2023)
Internship is the last course for all undergraduates in the Faculty of Business and Managements. All students are mandatory to undergo an internship for 6 months. An internship is a short-term work experience program to gain practical knowledge and skills in a specific field or industry. It provides students with hands-on learning opportunities, allowing them to apply theoretical knowledge in real-world settings. Internships can be paid or unpaid and are designed to offer valuable exposure to the professional environment, foster networking connections, and enhance the intern's resume. They serve as a bridge between academic education and professional life, helping individuals explore potential career paths, clarify their goals, and make informed decisions about their future endeavors. I managed to undergo my internship at Kumpulan Wang Persaraan (Diperbadankan) [KWAP], under Accounts and Finance Department. I started my internship on 1st March and ended on 15th August. In my opinion, KWAP is one of the best places for students to do an internship. KWAP is one of the GLIC in Malaysia and it is a great place to develop career and skills as interns are given real job tasks. In addition, KWAP also offers above average allowance and benefits for the interns. KWAP is a Malaysian government agency responsible for managing and safeguarding retirement funds for public sector employees in the country. Established in 2007, KWAP aims to ensure the financial security and welfare of retired civil servants by investing their contributions in a diversified portfolio of assets. As a significant institutional investor, KWAP plays a crucial role in the nation's economy, making long-term investments to generate returns and secure pension benefits for its members, contributing to the overall stability of Malaysia's retirement system. In this report, we can identify the SWOT analysis for KWAP. SWOT analysis is performed to assess the strengths, weaknesses, opportunities, and threats of a business or project. It helps organizations identify internal strengths and weaknesses, external opportunities and threats, enabling them to make informed decisions, capitalize on advantages, mitigate risks, and develop effective strategies for success.